2019
DOI: 10.1002/chir.23076
|View full text |Cite
|
Sign up to set email alerts
|

Efficient racemization of N‐phenylacetyl‐D‐glufosinate for L‐glufosinate production

Abstract: Most amino acids contain chiral centres and exist as both D‐enantiomer and L‐enantiomer. The optically pure enantiomer is often more valuable than the racemate. Enzymatic resolution provides an effective strategy to obtain optically pure amino acids but often results in large amounts of unwanted isomer. In this study, optically pure L‐glufosinate (L‐PPT) was obtained by coupling amidase‐mediated hydrolysis of N‐phenylacetyl‐D,L‐glufosinate with racemization of N‐phenylacetyl‐D‐glufosinate (NPDG), which exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…6 More recently, another method has been proposed to increase the proportion of L-phosphinothricin at up to 96% by coupling the amidase-mediated hydrolysis of N-phenylacetyl-D,L-phosphinothricin with racemization of N-phenylacetyl-Dphosphinothricin. 7 Field and laboratory experiments demonstrated that formulations with increased proportions of L-phosphinothricin provided similar levels of both grass and broadleaf weed control as well as lower crop injury for cotton and soybean compared to equivalent amounts of the L-isomer in the racemic mixture. 5 Glufosinate was first commercialized in the United States and Canada in 1993-1994 as a non-selective herbicide with broad spectrum of weed control.…”
Section: Discovery and Commercializationmentioning
confidence: 99%
See 1 more Smart Citation
“…6 More recently, another method has been proposed to increase the proportion of L-phosphinothricin at up to 96% by coupling the amidase-mediated hydrolysis of N-phenylacetyl-D,L-phosphinothricin with racemization of N-phenylacetyl-Dphosphinothricin. 7 Field and laboratory experiments demonstrated that formulations with increased proportions of L-phosphinothricin provided similar levels of both grass and broadleaf weed control as well as lower crop injury for cotton and soybean compared to equivalent amounts of the L-isomer in the racemic mixture. 5 Glufosinate was first commercialized in the United States and Canada in 1993-1994 as a non-selective herbicide with broad spectrum of weed control.…”
Section: Discovery and Commercializationmentioning
confidence: 99%
“…The conversion of PPOB into L‐phosphinothricin can also be performed enzymatically through glutamate dehydrogenase, with optimized affinity for glufosinate 6 . More recently, another method has been proposed to increase the proportion of L‐phosphinothricin at up to 96% by coupling the amidase‐mediated hydrolysis of N ‐phenylacetyl‐D,L‐phosphinothricin with racemization of N ‐phenylacetyl‐D‐phosphinothricin 7 . Field and laboratory experiments demonstrated that formulations with increased proportions of L‐phosphinothricin provided similar levels of both grass and broadleaf weed control as well as lower crop injury for cotton and soybean compared to equivalent amounts of the L‐isomer in the racemic mixture 5…”
Section: Discovery and Commercializationmentioning
confidence: 99%
“…Unreacted N -phenylacetyl- d -phosphinothricin was added into a round bottom flask with phenylacetic acid in a mole ratio of 1:1.2. , The racemization reaction was performed in an oil bath at 140, 150, and 160 °C. After completion of the reaction, the racemic N -phenylacetyl- d , l -phosphinothricin was recycled as the substrate for second-round enzymatic hydrolysis.…”
Section: Methodsmentioning
confidence: 99%
“…The optical purity of L-phosphinothricin was determined on an Agilent C18 column after derivatization with o-phthalaldehyde/Nacety-L-cysteine using 50 mM ammonium acetate (pH 5.7)/methanol (90:10, v/v) as the mobile phase at a flow rate of 1.0 mL min −1 . 14 The eluent was monitored at 232 nm, and the column temperature was set at 40 °C. The retention times of L-and D-phosphinothricin were 10.39 and 12.71 min, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…But, it often raised the problems of the complex synthesis process, high cost for the catalyst, and environmental pollution [5] . Recently, the biological method of synthesizing l ‐PPT has attracted more and more attention due to its advantages of low impact on the environmental, high rate of atom use, and high product yield, in which amidase, [6] nitrilase, [7] deacetylase, [8] amino acid dehydrogenase [9] and transaminase [10] were involved.…”
Section: Figurementioning
confidence: 99%